Peran Religiusitas dan Kecerdasan Emosional terhadap Resiliensi Penyintas Tsunami Selat Sunda - Sarbini Sarbini; Elisa Kurniadewi; Ridwan Santoso (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2021)
This study aims to examine the influence of religiosity and emotional intelligence on resilience of tsunami survivors in the Selat Sunda that occurred on December 22, 2018. This study used a quantitative correlational approach. Using accidental sampling technique, the participants were 62 tsunami survivors of Selat Sunda in Pandeglang, age ranged between 20-65 years, lost their homes, livelihoods, death of family/relatives or experienced physical illness/disability. This study used 3 instruments, including: The Centrality of Religiosity Scale (CRS), Goleman emotional intelligence measuring instrument, and Connor Davidson Resilience Scale (CD-RISC). The results showed that religiosity and emotional intelligence had a simultaneous effect on resilience with a percentage of 17. Partially, religiosity had no significant effect on resilience to tsunami survivors in the Selat Sunda in Pandeglang.